Vận dụng lí thuyết kiến tạo trong dạy học giải bài tập môn Toán lớp 11 với sự trợ giúp của máy tính cầm tay FX-580VN X - Bùi, Anh Kiệt; Trần, Văn Quân (Tạp chí Giáo dục, 2024)
In teaching Mathematics in high school, with the support of handheld computers, learners can handle simple to complex mathematical operations such as calculating logarithm values, limits of functions, calculating integrals,... quickly and accurately, minimizing learners' homework time. The research develops a process for applying constructivist theory in teaching and solving math exercises “Limits of functions” (Math 11) and illustrates this process in solving some specific problems. The steps of the teaching process are to help students quickly solve math exercises, especially multiple-choice exercises about the limits of functions accurately. If teachers effectively use the process in teaching the lesson “Limits of functions”, it will help students develop learning competences, especially the competence to use tools and means to learn Mathematics.